2016
DOI: 10.1161/circinterventions.116.003698
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Everolimus-Eluting Bioresorbable Vascular Scaffolds Versus Drug-Eluting Metallic Stents

Abstract: Background-The performance of everolimus-eluting bioresorbable vascular scaffold (BVS) versus drug-eluting metallic stent (DES) in the same individual receiving multilesion percutaneous coronary intervention (PCI) remains poorly studied. This report investigates the intraindividual performance of BVS and DES in patients receiving multilesion PCI and follow-up angiography. Methods and Results-Data of patients undergoing BVS implantation for de novo lesions from 2012 to 2014 at 2 centers in Munich, Germany, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Consistent with previous data 10 , we found a lower minimum lumen diameter after PCI with Absorb as compared to EES, reflecting the intrinsic limitation of this technology. However, the treatment groups did not differ for this parameter at angiographic follow-up, suggesting a relatively stable mechanical behaviour of Absorb in STEMI patients, without instances of late recoil as previously observed 11 . Second, the risk for DOCE at 12 months was similar with Absorb and EES.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with previous data 10 , we found a lower minimum lumen diameter after PCI with Absorb as compared to EES, reflecting the intrinsic limitation of this technology. However, the treatment groups did not differ for this parameter at angiographic follow-up, suggesting a relatively stable mechanical behaviour of Absorb in STEMI patients, without instances of late recoil as previously observed 11 . Second, the risk for DOCE at 12 months was similar with Absorb and EES.…”
Section: Discussionsupporting
confidence: 71%
“…CAD is the leading cause of mortality and morbidity in the developed world ( 13 ). Numerous improvements have been made in coronary angioplasty, including balloon angioplasty, stenting and CABG, although a metallic scaffold device, alone or in combination with drug eluting stents (DESs) is considered to be the most effective method of treating CAD ( 14 ). However, studies have suggested that DESs delay re-endothelialization, which is important for the prevention of restenosis and stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Interventions, Cassese et al 5 report an intraindividual comparison of the performance of everolimus-eluting bioresorbable vascular scaffolds (BVS) versus durable metallic everolimus-eluting stents (DES) in the same individual but in different arteries. The 90 patients undergoing percutaneous coronary intervention to 239 lesions were assigned, at operator discretion, to receive a BVS (n=112) or DES (n=127).…”
Section: See Article By Cassese Et Almentioning
confidence: 99%
“…However, after adjustment for baseline angiographic differences, device type no longer significantly influenced late lumen loss. 5 This is not a randomized trial. Although the contribution of patient-related factors that may influence outcome between groups was controlled for in the study design, there were important baseline lesion-related differences.…”
Section: See Article By Cassese Et Almentioning
confidence: 99%
See 1 more Smart Citation